Heavenly masters two thousand years of the Daoist state - Goossaert, Vincent 1969- (New Daoist studies, 2021)
The origins of modern Daoism can be traced to the Church of the Heavenly Master (Tianshidao), reputedly established by the formidable Zhang Daoling. In 142 CE, according to Daoist tradition, Zhang was visited by the Lord on High, who named him his vicar on Earth with the title Heavenly Master. The dispensation articulated an eschatological vision of saving initiates-the pure, those destined to become immortals-by enforcing a strict moral code. Under evolving forms, Tianshidao has remained central to Chinese society, and Daoist priests have upheld their spiritual allegiance to Zhang, their now divinized founder.